Anonimi: notitia del valore delle note del canto misurato - Carapetyan, Armen (American Institute of Musicology, 1957)
Reproduced from the manuscript Redi 71 of the Biblioteca Mediceo-Laurenziana at Florence.
Keywords: Music theory